2020
DOI: 10.31943/mathline.v5i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kemampuan Pemahaman Matematis Siswa Menggunakan Worked Example

Abstract: Artikel ini bertujuan untuk menelaah dan menganalsis peningkatan kemampuan pemahaman matematis siswa setelah pembelajaran menggunakan worked example . Metode yang digunakan adalah metode pre-eksperimen dengan one group  pretest postest design. Sampel dalam penelitian ini adalah siswa SMP kelas VIII-J SMP Negeri 1 Jalaksana. Peningkatan kemampuan pemahaman matematis siswa diperoleh dari nilai n-gain. Teknik analisis data yang digunakan meliputi uji normalitas, dan uji t satu sampel. Dari data hasil penelitian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on the score category in the pretest and computational thinking skills in each experimental class, there is a significant improvement in terms of computational thinking skills when worked examples strategy is used either with or without voice notes. Noorfitriani and Rosyid (2020) It was found that the students can break down the problem into a simpler form. The students can identify the function of f(x) and f(x+h) from the questions presented as a source of searching for the first derivative by the definition given.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the score category in the pretest and computational thinking skills in each experimental class, there is a significant improvement in terms of computational thinking skills when worked examples strategy is used either with or without voice notes. Noorfitriani and Rosyid (2020) It was found that the students can break down the problem into a simpler form. The students can identify the function of f(x) and f(x+h) from the questions presented as a source of searching for the first derivative by the definition given.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Santosa, Rafianti, & Yulistiany (2022) stated that there were different abilities in solving mathematical problems between students who received worked-example and expository learning methods; (2) There are differences in the ability to solve mathematical problems between students who have high and low initial abilities (Santosa et al, 2022). Meanwhile, Noorfotriani & Rosyid (2020) stated that the increase in students' mathematical understanding abilities using worked examples was in the high category (Noorfitriani & Rosyid, 2020).…”
Section: Introductionmentioning
confidence: 99%